Effects of Variety and Spacing on Growth Characters of Hybrid Maize - E. C. , Enujeke (Asian Journal of Agriculture and Rural Development, 2013)
This study was carried out in Teaching and Research Farm of Delta State University, Asaba Campus from March, 2008 to June, 2010 to evaluate the effects of variety and spacing on growth characters of hybrid maize. It was a factorial experiment carried out in a Randomized Complete Block Design (RCBD) with three replicates. Three hybrid maize varieties were evaluated under three different plant spacing for such growth characters as plant height, number of leaves, leaf area and stem girth. The results obtained during the 8th week after sowing indicated that hybrid variety 9022-13 which had mean plant height of 170.0cm number of leaves of 13.2, leaf area of 673.2cm2 and stem girth of 99.4mm was superior to other varieties investigated. With respect to spacing, plants sown on 75 cm x 15 cm had higher mean height and number of leaves of 176.7 cm and 13.8, respectively while plants sown on spacing of 75 cm x 35 cm had higher mean leaf area of 713.7 cm2 and stem girth of 99.4mm, respectively. Results of interaction showed that variety and spacing were significantly (P<0.05) different in 2008 and 2009. Based on the findings of this study, it is recommended that (i) hybrid variety 9022-13 be grown in the study area of enhanced growth characters which interplay to improve grain yield of maize (ii) spacing of 75 cm x 35 cm be used to enhance increased stem girth and leaf area whose photosynthetic activities could positively influence maize yield.